Eventos que configuran la noción de victima cómo sujeto de reconocimiento dentro de discursos autorizados en el ámbito académico, social y estatal, desde 1980 hasta 2011, en el marco del conflicto Armado en Colombia (2017)
Introduction: The research explores the configuration of the concept Victim as subject of recognition within the framework of the Colombian Armed Conflict, was analyzed and explained, through the Authorized Social and Academic Discourses of two paradigmatic events chosen from 1980 to 2011: The Taking of the Palace of Justice (1985) and La Massacre de Mapiripán (1997), to later contrast them with the Law of Victims and Land Restitution - ley 1448 of 2011 -. Objective: To analyze two paradigmatic events within the framework of the Armed Conflict that shape the notion of victim as a subject of recognition within authoritative discourses in the academic, social and state spheres. Method: Identification, compilation and documentary analysis of information found on the categories studied in Redalyc database, Research and Popular Education Center -CINEP-, Newspaper from below and Corporación Nuevo Arcoíris Results: construction of three types of victims was achieved in which it can be configured as a subject of recognition: Direct Victims, Violent Victims and Symbolic Victims, in addition, identified some characteristic features of the victims as recognized subjects and a special premise on Integral reparation to victims.